NITROGEN ABUNDANCE FROM THE ULTRAVIOLET NH BANDS - Yakovina, L. A.; Pavlenko, Ya. V. (Одеські астрономічні публікації, 2017)
Data for NH bands region 336 nm from CD-ROM’s N1 and N18 of Kurucz’s database are tested and corrected using the spectrum of the Sun as a star. The nitrogen abundance indicators are selected for spectral resolutions δg = 0.0025 nm and 0.02 nm. Using this indicators we derived [N/Fe] = 0 in atmosphere of КО giant γ1 Leo. The accuracy of nitrogen abundance estimations is considered.